Physiological Response of Dairy Cows in Mandiri Sejahtera Cijeruk Livestock Group Based on Microclimate in Real Time Using NB IoT - Mubarrok, Muhammad Tirta; Yani, Ahmad; Komala, Iyep; Gampur, Yasintus Basmadarto (Faculty of Animal Science, Universitas Brawijaya, 2025)
The research aimed to compare microclimate data using the Internet of Things (IoT) system with the physiological response data of dairy cows as a reference for modifying the microclimate conditions of dairy cow barns in highlands. The study used ten lactating dairy cows in the Cijeruk Independent Livestock Group. Temperature, humidity, ammonia, wind speed, lighting, and THI were recorded in real time for 24 hours. The observed physiological responses were rectal temperature (RT), heart rate (HR), respiratory rate (RR), and heat tolerance coefficient (HTC). The microclimate and physiological response data were analyzed using descriptive statistical methods and Post Hoc statistical tests using the Statistical Package for the Social Sciences (SPSS). The results of the environmental conditions using Narrowband (NB)-IoT (D-Ruminant) showed maximum values (Temperature 29.03±2.27 at 12:30 PM, Humidity 83.75±4.09 at 07:30 AM, Ammonia 0.16±0.11 at 05:30 PM, Lighting 21238±11082 at 12:30 PM, Wind Speed 2.15±1.83 at 12:30 PM, and THI 78.92±1.96 at 12:30 PM). And the minimum values for the environmental conditions (Temperature 24.06±0.49 at 07:30 AM, Humidity 65.59±14.4 at 12:30 PM, Ammonia 0.11±0.04 at 12:30 PM, Lighting 425±237, Wind Speed 1.47±1.16 at 07:30 AM, and THI 73.72±0.94 at 07:30 AM). The physiological responses and HTC showed maximum levels (Rectal Temperature 38.3±0.44 at 12:30 PM).